1987
DOI: 10.1080/01647958708683476
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of eggs ofDermatophagoides pteronyssinus(Acari: Pyroglyphidae) by natamycin and imidazoles in Vitro

Abstract: The potential ovicidal activity of natamycin and four imidazoles was investigated with levilite-diatom powder and water as controls. All products tested prevented larval hatching, but not embryonic development. Irregular distribution of the products on the sprayed eggs was noted, except for natamycin. The eggs appeared surrounded in crystal formations or particle clusters. The random nature of these phenomena explains the greatly varied resuits. Its superior dispersion gives natamycin a clear advantage over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…Major insects pest of stored maize include Sitophilus zeamais (Motschulsky), Rhyzopertha dominica (Fabricius) and Tribolium confusum (Jacquelin du Val) (Mejía, 2007). The constant migration of insect populations within the maize agroecosystem contributes to the dispersal of viable fungal spores of several species (Saint Geroges-Gridelet, 1984). A previous study conducted in stored maize showed a high percentage of live S. zeamais and R. dominica contaminated with Aspergillus section Flavi (Nesci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Major insects pest of stored maize include Sitophilus zeamais (Motschulsky), Rhyzopertha dominica (Fabricius) and Tribolium confusum (Jacquelin du Val) (Mejía, 2007). The constant migration of insect populations within the maize agroecosystem contributes to the dispersal of viable fungal spores of several species (Saint Geroges-Gridelet, 1984). A previous study conducted in stored maize showed a high percentage of live S. zeamais and R. dominica contaminated with Aspergillus section Flavi (Nesci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%